Advances in Requirements Engineering for Well-Being, Aging, and Health: A Systematic Mapping Study - Almeida, Camila; Freire, Sávio; Mendonça, Manoel; Spínola, Rodrigo (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2025: Anais do XXIV Simpósio Brasileiro de Qualidade de SoftwareDO - 10.5753/sbqs.2025.14964, 2025)
Context. The increasing focus on well-being, aging, and health (WBAH) is impacting various fields, including Requirements Engineering (RE). This is particularly relevant, as RE involves defining, documenting, and managing software system requirements to ensure that developed systems effectively address user needs. However, there remains a limited understanding of how RE practices can be tailored to create WBAH-centric systems. Aims. This study aims to explore the current landscape of RE practices used in the development of software systems that support WBAH. Method. We conducted a systematic mapping study, analyzing articles from reputable conferences and journals. Results. Our review identified 57 articles published between 2013 and 2024 that examine RE efforts related to specifying and documenting WBAH systems. The predominant topics discussed include usability and evaluation techniques, elicitation and modeling methods, security and privacy concerns for healthcare applications, and the adaptation of RE for specific populations, such as the elderly. Conclusion. This study highlights significant knowledge gaps that present opportunities for further investigation by RE researchers.